Le goût du fruit défendu ou de la lecture de l'albanais dans l'Empire ottoman finissant - Nathalie Clayer (Revue des Mondes Musulmans et de la Méditerranée, 1999)
From the mid-sixteenth century until the Young Turk Revolution, the production of books in Albanian, which were circulated in the Ottoman Empire, passed through three stages : up until the beginning of the nineteenth century, a few religious books were published for a restricted public ; the three first quarters of the nineteenth century can be considered as a period of transition during which the « sacred book » gave way to the « national book » ; the national book developed during the third stage, between 1878 and 1908. The production and circulation of Albanian books owe a lot to Albanians living abroad and to foreign help (especially from some governments such as the Austro-Hungarian Empire, as well as from the activities of Protestant missionaries).Because of the links between these developments and the building of an Albanian national identity, the diffusion of this literature increased, but with more and more difficulties. There were external reasons for this, such as Ottoman censorship, but also internal causes, above all, the great religious, regional and cultural disparities amongst the Albanian population.